2020
DOI: 10.1177/0009922819898182
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison Study of Primary Care Utilization and Mental Health Disorder Diagnoses Among Children In and Out of Foster Care on Medicaid

Abstract: The purpose of this study was to compare the utilization of primary care services and presence of mental health disorder diagnoses among children in foster care to children on Medicaid not in foster care in a large health system. The data for this study were analyzed from a clinical database of a multipractice pediatric health system in Houston, Texas. The sample included more than 95 000 children covered by Medicaid who had at least one primary care visit during the 2-year study period. The results of the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Previous studies have found a strong association between foster care and mental health problems in children [ 23 25 ]. The results in this study showed that the probability of utilizing child protection services increased immediately during the quarter of the initial diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have found a strong association between foster care and mental health problems in children [ 23 25 ]. The results in this study showed that the probability of utilizing child protection services increased immediately during the quarter of the initial diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…One reason could be that mental health diagnoses are typically more prevalent in vulnerable populations. For example, the probability of mental health diagnoses in children placed in out-of-home care (foster care) is considerably higher [ 23 25 ]. Despite the higher utilization of services, treatment gaps seem to persist in mental health conditions [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Instead, electronic health records (EHRs), interviews and parent/self-reports, chart reviews, and questionnaires were more typically used. 4,5,[21][22][23][24] Although not without its limitations, claims data allow us to ascertain all diagnoses for which a claim was submitted for all types of health care providers and locations, including emergency, inpatient, urgent, primary, specialty, and home care. This is more comprehensive than the use of an EHR, in which data are limited to encounters in that specific health clinic or system.…”
Section: Discussionmentioning
confidence: 99%